The Effect of Carbon Management Accounting, Competitive Business Strategic and Carbon Emission Disclosure on Company Performance Moderated by Green Intellectual Capital - Whittleliang Hakki, Tandry; Akwila, Karvicha; Jurjanta, Priccilya (DINASTI RESEARCH, 2024)
Several climate changes or extreme weather that often occur throughout the world in recent years, this directly makes society focus and increases the level of awareness of climate change that occurs. warming. Global warming is a hot issue and has become a public focus to be discussed in several world organization forums in recent decades. Global warming can be caused by the main factor, namely carbon emissions. This study aims to examine the effect of Carbon Management Accounting, Competitive Business Strategy, and Carbon Emission Disclosure on Company Performance moderated by Green Intellectual Capital. This study took the research population in energy sector companies. The type of data used in this study is secondary data in the form of company financial reports that are used as samples. The research method used in this study is a quantitative research method. The sample was selected using the purposive sampling method. For hypothesis testing, this study uses multiple linear regression analysis. Based on the results of this study, it shows that Carbon Management Accounting and Carbon Emission Disclosure have an effect on Firm Performance, but Carbon Emission Disclosure has no effect on Firm Performance. Green Intellectual Capital strengthens the influence of Carbon Management Accounting on Firm Performance and Green Intellectual Capital does not strengthen the influence of Competitive Business Strategy and Carbon Emission Disclosure Strategy on Firm Performance.